Active recovery vs sodium bicarbonate: impact on lactic acid removal following a specific judo effort - Trajkovic, N.; Sancic, J.; Scruton, A.; Prosoli, R.; Stefan, L.; Sporis, G.; Madic, D. (Archives of Budo, 2017)
Background and Study Aim: Combat sports such as judo are known to be extremely high demanding which can result with a high level of lactic acid. Because of that recovery is a crucial part of the preparation for competitive judo. The aim of this study was the effectiveness of active recovery and sodium bicarbonate to the removal of lactic acid after a judo match simulation (JMS) and Specific Judo Fitness Test (SJF).